Comparison of ratios combination calcium hydroxide Ca(OH)2 with red pine (Pinus densiflora) of viscosity - Wahjuningrum, Dian Agustin; Mooduto, Latief; Subiyanto, Ari; Prasita, Shafa; Yuanita, Tamara (Faculty of Dental Medicine Universitas Airlangga, 2021)
Background: Calcium hydroxide is a gold standard for root canal sealing material. However, there are many defects in calcium hydroxide that have prompted many researchers to look for alternative materials, including natural origin ingredients. Red pine (Pinus densiflora) is often used in dentistry for its antioxidant and antibacterial properties. The mixture of calcium hydroxide and red pine has never been achieved before. One of the criteria for material sealing is that the channel should be fully sealed with high flow ability and low viscosity. Therefore, this research is performed to analyze the viscosity value of the mixture of calcium hydroxide and red pine (Pinus densiflora). Purpose: Knowing the difference in viscosity of the combination of calcium hydroxide and red pine with a ratio of 1:1, 1:1.5, and 1:2. Methods: This study used four treatment groups, with each group consisting of 8 replications. Group 1 was a combination of calcium hydroxide and red pine with a 1: 1, group 2 the ratio was 1: 1.5, group 3 had the ratio 1: 2, and the positive control group used calcium hydroxide and a sterile aquadest. Calcium hydroxide in powder form and an extract of red pine in liquid form are mixed according to the ratio. The viscosity value is measured using a viscosity tester, namely the Brookfield Viscometer. Results: The control group had a lower viscosity than group 3, group 3, and group 2 than group1. Conclusion: Combination of calcium hydroxide and red pine with a ratio of 1:2, the lowest viscosity was obtained compared to the ratio of 1: 1 and 1: 1.5.